2019
DOI: 10.13187/ejced.2019.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Intelligence of the Jordan Teachers and University Students from the Hashemite University: Comparative Study

Abstract: The present study aimed at comparing the level of cultural intelligence among teachers and university students, and to define whether there are statistically significant differences in the level of cultural intelligence due to gender variables. The sample consisted of 300 teachers and 400 students at the Hashemite University, chosen by random selection, and data collected using the Cultural Intelligence Scale. Results of the study showed a high level of cultural intelligence among teachers and university stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For example, Alavinia & Mollahossein (2012) found a positive relationship between learners' EI and their use of metacognitive strategies. Sharei et al (2012) found that meta-cognition, and EI contribute significantly to the prediction of problem-solving ability and Mahasneh et al (2019) indicated that generally high level of cognition regulation, understanding of cognition and cognition processing meta-cognition are related to a high levels of emotional knowledge, emotion regulation, empathy, and social commitment EI., as Carpenter et al (2019) showed increases in metacognitive calibration were observed with adaptive training, which generalized to untrained stimuli and an untrained task, indicating the potential for a domain-general enhancement of metacognitive abilities in EI., metacognition training has a positive effect on decreased negative emotions general wellbeing (Van Cappellen et al, 2022) and increased social bounds (Rafie et al, 2020;Oraki et al, 2022). Moreover, Drigas et al (2021) presented the metacognitive and meta emotional skills needed to develop the individual's EI based on the pyramid model of emotional intelligence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Alavinia & Mollahossein (2012) found a positive relationship between learners' EI and their use of metacognitive strategies. Sharei et al (2012) found that meta-cognition, and EI contribute significantly to the prediction of problem-solving ability and Mahasneh et al (2019) indicated that generally high level of cognition regulation, understanding of cognition and cognition processing meta-cognition are related to a high levels of emotional knowledge, emotion regulation, empathy, and social commitment EI., as Carpenter et al (2019) showed increases in metacognitive calibration were observed with adaptive training, which generalized to untrained stimuli and an untrained task, indicating the potential for a domain-general enhancement of metacognitive abilities in EI., metacognition training has a positive effect on decreased negative emotions general wellbeing (Van Cappellen et al, 2022) and increased social bounds (Rafie et al, 2020;Oraki et al, 2022). Moreover, Drigas et al (2021) presented the metacognitive and meta emotional skills needed to develop the individual's EI based on the pyramid model of emotional intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Theory and research in metacognition have introduced as a basis for understanding and treating psychological dysfunction (Wells & Cartwright-Hatton, 2004). Henson and Eller (1999), Lindstrom (1995), andBruer (1994) suggest that metacognition attempts to increase the awareness of thinking procedures and methods, thereby helping the learner to control, regulate, guide and master the learning processes, the ultimate purpose being the appreciation and comprehension of learning strategies (Mahasneh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This result is a little surprising due to the difference in life paths and experiences of the two groups. In a contradictory way, Mahasneh and Gazo [56] obtained results that indicated significant differences in the cognitive and behavioral dimensions, with lower values for students. However, in the overall value of CQ, they did not find significant differences either.…”
Section: Level Of Cqmentioning
confidence: 97%
“…The international nature of the professional activity of higher education institution staff, despite always having had an internationalization component, is nowadays very intense, whether through mobility initiatives, research activity or the growing presence of international students in classrooms. Only one study developed in Jordan assessed whether there were differences between these two groups [56].…”
Section: Cultural Intelligence In Higher Education Institutionsmentioning
confidence: 99%
“…At the same time, they could concern one component. In Mahasneh's research (Mahasneh et al, 2019), it was a CQ motivational dimension. Engle and Nehrt (2012) and Ward, Festcher (2008) research did not state any statistically significant differences in cultural intelligence due to gender variables.…”
Section: Theoretical Foundation and Development Of Hypothesesmentioning
confidence: 99%